2017
DOI: 10.1093/icesjms/fsx232
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in offspring quality and individual reproductive output in a broadcast-spawning marine fish

Abstract: The protracted spawning period of broadcast-spawning marine fishes has potential to generate considerable variability in metrics of individual reproductive output. We undertook a temporally detailed genetic study of larvae produced by Atlantic cod (Gadus morhua) from two spatially proximate populations spawning under controlled semi-natural conditions over 94 days. Based on daily samples of larvae (n = 4489 in total), we document fine-scaled temporal changes in, and correlates of, offspring phenotype and repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The ecotype proportions among the adult cod collected from inner and outer Risør fjord were consistent with a long-term survey of juvenile ecotype composition in this fjord system (Knutsen et al, 2018). We show that, provided the opportunity in semi-natural laboratory conditions, there is potential for substantial reproduction between cod inhabiting the inner and outer parts of Risør fjord (previously shown by Roney, Oomen, Knutsen, Olsen, & Hutchings, 2018b) and between cod of fjord and North Sea ecotype (first documented here). The range of the fjord ecotype is nearly completely overlapped by that of the North Sea ecotype in coastal areas and the presence of eggs, larvae, and adults in spawning condition has previously suggested that the North Sea cod reproduce there (Jorde, Kleiven, et al, 2018; Jorde, Synnes, et al, 2018; Knutsen et al, 2018; Rogers et al, 2014).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The ecotype proportions among the adult cod collected from inner and outer Risør fjord were consistent with a long-term survey of juvenile ecotype composition in this fjord system (Knutsen et al, 2018). We show that, provided the opportunity in semi-natural laboratory conditions, there is potential for substantial reproduction between cod inhabiting the inner and outer parts of Risør fjord (previously shown by Roney, Oomen, Knutsen, Olsen, & Hutchings, 2018b) and between cod of fjord and North Sea ecotype (first documented here). The range of the fjord ecotype is nearly completely overlapped by that of the North Sea ecotype in coastal areas and the presence of eggs, larvae, and adults in spawning condition has previously suggested that the North Sea cod reproduce there (Jorde, Kleiven, et al, 2018; Jorde, Synnes, et al, 2018; Knutsen et al, 2018; Rogers et al, 2014).…”
Section: Discussionmentioning
confidence: 53%
“…The multiplexes were modified from Delghandi et.al. (2003) (Multiplex 1) and Dahle et al (2006) and Glover et al (2010) (Multiplex 2), and were previously used for parental assignment of offspring from the same broodstock as that used in the present study (Roney, Oomen, Knutsen, Olsen, & Hutchings, 2018b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite similarity in terms of number of individuals, average body size, sex ratio, initiation of spawning period, and body condition, cod originating from outer Risør fjord were less reproductively successful than those from inner Risør fjord, a finding consistent for both males and females. Based on data reported in a separate study (Roney, Oomen, Knutsen, Olsen, & Hutchings, ), duration of the spawning period was the same for males but longer for inner‐fjord females.…”
Section: Discussionmentioning
confidence: 99%
“…A strategy of broadcast spawning on multiple spawning grounds, multiple times (Kjesbu, 1989 ) and over prolonged periods (Hutchings & Myers, 1994 ; Kjesbu et al, 1996 ) might act as a portfolio effect by reducing the risk of complete reproductive failure. The production of multiple egg batches within a spawning season, the number of which increases with female weight and body size (Kjesbu et al, 1996 ; Roney et al, 2018 ), could enable a batch spawner to spread the environmental risk among its offspring and mitigate the fitness consequences of environmental fluctuations. As a trade‐off in diversification, the variance in reproductive output of a multiple‐batch spawner could be lower, boosting the across‐generational geometric mean fitness, at the expense of producing a lower average number of offspring.…”
Section: Introductionmentioning
confidence: 99%